Android-based member card "DigiCard" storage application. Issue 1 (February 2020) - Agusrianto, K; Chandra, T; Wijono, A T; Sari, A C
Abstract: The purpose of this research is to develop mobile application that can store cards to digital form base on Android, that being used by user which have member card as a media to getting rid from the card being damaged or stolen. In the making of this application, literature review and questionaire are being used as data colletion methodology and extreme programming is being used as research methodology. The goals in making this application is the application can store a physical card into digital form, scan barcode from member card, show realtime promo, online registration, and showing nearest retail location using Android Studio with Java programming language. The conclusion of this research is, this application can help the user as media to avoid careless user in using the card in physical form.